2xThru De-Embedding Challenges - Oniani, Salome (Journal of Electronics and Electrical Engineering, 2025)
Fixture de-embedding is a method used to remove unnecessary effects introduced by test fixture in measurement, allowing for the accurate extraction of S-parameters for the device under test. Among the known fixture de-embedding techniques, 2xThru de-embedding is one of the most widely used methods, both commercially and in scientific research, due to its efficiency and ease of implementation. By reducing the number of measurements required, 2xThru de-embedding maintains its popularity compared to traditional methods. The method is standardized by the "IEEE Standard for Electrical Characterization of Printed Circuit Board and Related Interconnects at Frequencies up to 50 GHz", which defines the design requirements for test fixtures and requires a long transmission line in the center of the 2xThru structure. The presented paper discusses cases when 2xThru violates the norms given by the standard, namely when the transmission line in the center of the 2xThru structure is too short, as a result of which it is obtained that the discontinuity in the fixture does not vanish before it reaches middle point of the structure. The paper analyzes these cases, and it is accepted that even in the case of such devices, using existing de-embedding tools, it is possible to obtain correct left and right fixtures.